Study of Hydrodynamics and Overall Gas Hold Up Validation in Bubble Column by Computational Fluid Dynamics - Yukh Ihsana; Sugeng Winardi; Tantular Nurtono (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2020)
The study of overall gas hold up has been carried out experimentally with the bed expansion. The superficial gas velocities used for the experiments are 6.369 m/s and 10.616 m/s. The experiment is carried out in a bubble column with inside diameters of 7 cm and a height of 100 cm. Gas from the gas cylinder is supplied through a distributor consisting of a perforated plate and glass beads. The perforated plate has a hole diameter of 1 mm and 0.5 mm. Computational Fluid Dynamic (CFD) using a Eulerian coupled with Population Balance model is developed to predict overall gas hold up and bubble size distribution. The effect of superficial gas velocity, perforated plate diameter, gas properties, and initial liquid level on gas hold up were studied. The use of population balance can significantly improve the overall gas hold-up results compared to constant bubble diameter. It is found that several operating conditions affect the whole gas hold up, namely initial liquid level, superficial gas velocity, and differences in gas properties. While the influence of the difference in perforated plate diameter to overall gas holds up, results are small compared to other operating conditions.